Some questions about the relationship between advertising, consumerism and Good Living - Canga Sosa, Manuel (2017)
This paper holds a reflection on the role played by advertising speech in today's society, taking as a reference some of the ideas that have been discussed regarding the Good Living and questioning also, from a theoretical and critical perspective, the way mankind is related with nature. The phenomenon of consumerism is questioned founding a debate about the responsibility of citizens, who ought to be aware of the risks of certain attitudes and actions for the whole natural environment.